Challenges faced by the laboratory professionals during COVID-19 pandemic at tertiary care hospital, Kathmandu, Nepal (Grande Medical Journal, 2021)
COVID-19 pandemic has affected most sectors of health care services operations and staffs. National lockdown also negatively affected the number of OPD patients and non-essential medical services. Routine laboratory tests declined drastically during the lockdown period. Outsourced tests, quality control, reagent demand and supply, reagent, maintenance of equipment were negatively affected during the pandemic. Staff members faced immense pressure to maintain workplace safety and provide the best service with limited resources. To counter the effects of the pandemic, different strategies and policies were implemented at the department of the laboratory at Grande International Hospital. The limited laboratory workers were divided into different groups as duty shifts to reduce the chances of infection among the co-workers. In this article, we share the challenges and experiences at our work in six-month duration during the pandemic during the first lockdown enforced by the Government of Nepal